DISTRIBUTIVE JUSTICE AND INCLUSIVE SOCIETY: ROLE OF RELIGION IN THE EQUITABLE DISTRIBUTION OF WEALTH - Ottuh, P. O. O.; Ottuh, J. A.; Aitufe, V. O. (European Scientific Journal, ESJ, 2014)
In this treatise, some aspects of the relationship of religion to economic questions are examined, particularly those associated with wealth distribution, because of their inevitably close association with societal common good. Utilitarian philosophers argued that all decisions could be made according to the principal of the greatest “utility,” or benefit, to the greatest number of people. In this work therefore, the authors examined how it related to concepts of justice and fairness and to the doctrine of utility with the aim of building an inclusive society. The study noted that the ways in which scarce time, skill, and resources are used are often affected by religiously motivated decisions. For instance, a study of a Hindu caste, or a medieval manor, or some labour unions may reveal that economic questions concerning the production of goods and services are conditioned by religious values. A second economic question – the description of the way in which comparative values are ascribed to be products of society – is also influenced, at least to a small degree, by religious considerations. Some goods and services are worth more, have a higher economic value, because they have a religious value, and others are worth less because religion places a negative value upon them. The study discovered that religion affects the demand side of the familiar supply demand equation and on the other hand, may influence the supply side, if the values it upholds encourage or discourage the production of various goods and service.